Design for smelling. - Gopel, W. (IEEE spectrum)
On our best days-without head colds, for example-and with a time out between sniffs, we can note the presence of and distinguish among 10000 airborne molecules or molecular compounds, sometimes when they amount to only a few molecules per trillion. Here, the authors present a quick tour of the route from molecule to smell. They correlate many of the discrete physiological steps with engineering ones, ranging from sampling, signal processing and amplification all the way to neural net computation